Modern informal empires - Fisher, Colin (Henry Stewart Talks, 2020)
This case study looks at modern informal empires, in which multinational corporations take on sovereign powers in developing areas, or areas of geopolitical instability to further their own agenda, using the BTC Pipeline as an example.